Water stress effect on hydraulic architecture, biomass partitioning, and gas exchange of four different olive cultivars - Imperiale, Valeria; Caruso, Tiziano; Ioppolo, Antonino; Carella, Alessandro; Massenti, Roberto; Marra, Francesco Paolo (Frontiers in Plant Science, 2025)
Olea europaea L. is considered a very resilient species to water deficits. Climate change, characterized by warmer summers and drier winters, may challenge even this adaptable species, potentially making once-suitable areas less viable for cultivation. Identifying cultivars with enhanced drought tolerance is essential for the future of olive growing. This study aimed to evaluate the water stress response of four olive cultivars: Biancolilla, Calatina, Nocellara del Belice, and Koroneiki, by analyzing their physiological traits and hydraulic properties. Potted plants were subjected to three irrigation treatments: T20, T50, and T100, corresponding to 20%, 50%, and 100% of crop evapotranspiration over approximately two months. Midday stem water potential and gas exchange were monitored throughout the trial. At the end of the experiment, plants were analyzed using a High-Pressure Flowmeter (HPFM) to measure hydraulic conductance (k) in leaves, shoots, trunks, and roots, providing insights into the plant’s hydraulic architecture. On these bases, the study aimed to identify strategies that different cultivars use to handle water stress. Biomass distribution and growth were significantly affected by cultivar and irrigation, with reductions occurring under severe stress, particularly in the shoots and leaves, while root biomass remained relatively stable. The relative stability of the root system and changes in canopy-to-root ratios highlight adaptive responses aimed at maintaining water uptake and ensuring stress resilience. ‘Calatina’ and ‘Nocellara del Belice’ showed less sensitivity to irrigation levels, maintaining relatively stable dry matter across all organs and treatments, while ‘Biancolilla’ and ‘Koroneiki’ exhibited the opposite. Different relative allocation strategies were evident: ‘Calatina’ prioritized shoot and leaves biomass and showed dwarfing growth; ‘Biancolilla’ invested more in trunk development, as well as ‘Nocellara del Belice’; ‘Koroneiki’ focused more resources on roots. Distinct hydraulic strategies emerged among the cultivars: ‘Koroneiki’ maintained high conductance in aerial parts, supporting sustained photosynthesis and growth; ‘Calatina’ adopted a conservative approach, prioritizing root conductance and limiting transpiration; while ‘Biancolilla’ and ‘Nocellara del Belice’ exhibited intermediate, balanced responses. These findings confirm the strong link between hydraulic architecture and physiological performance, offering insight into cultivar-specific responses to water stress and growth potential.